Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2005
DOI: 10.1145/1054972.1055009
|View full text |Cite
|
Sign up to set email alerts
|

Discrete acceleration and personalised tiling as brain?body interface paradigms for neurorehabilitation

Abstract: We present two studies that have advanced the design of brain-body interfaces for use in the rehabilitation of individuals with severe neurological impairment due to traumatic brain injury. We first developed and evaluated an adaptive cursor acceleration algorithm based on screen areas. This improved the initial design, but was too inflexible to let users make the most of their highly varied abilities. Only some individuals were well served by this adaptive interface. We therefore developed and evaluated an ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Millions of people suffer from severe impairments due to physical, sensorial, or mental damage [1]. When neuromuscular channels that permit communication between brain and environment are affected, partial or total muscle control may be lost.…”
Section: Introductionmentioning
confidence: 99%
“…Millions of people suffer from severe impairments due to physical, sensorial, or mental damage [1]. When neuromuscular channels that permit communication between brain and environment are affected, partial or total muscle control may be lost.…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained in summative methods should be tested using statistical methods, statistical significance, hypothesis validation, null hypothesis etc. Previous research [18] showed how five out of ten were unable to participate due to the visual impairment. This new research conducted at the Low Vision Unit of the National Eye Hospital (Colombo) for participants aged between seven and seventy were able to say 'yes' or 'no' using the brain body interface with seventy five percent consistency.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…With an external input device for brain waves this interface can be used for the brain injured during speech therapy. Gnanayutham and his team [16] designed and developed a soft keyboard for non-verbal quadriplegic brain injured persons. Future research in this area could connect brain waves to the interface developed in this research thereby taking this research to the next stage where the brain injured non-verbal community could be integrates into this research.…”
Section: Resultsmentioning
confidence: 99%